(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This research aims to study the estimation of the hidden economy using the currency demand method, with an applied study on the Kingdom of Saudi Arabia during the period (2012 – 2023). It is based on basic hypotheses stating the existence of a positive relationship between the tax burden and the size of the hidden economy, and a positive relationship between per capita national income and the hidden economy. The study also assumes that the relationship between the inflation rate and the hidden economy is negative. Using a descriptive and analytical approach through an econometric model, the study allows for estimating the size of the hidden economy in the Kingdom of Saudi Arabia during the period (2012 – 2023), relying on macroeconomic variables. The research results showed a significant positive relationship between taxes and the hidden economy, and a positive and significant effect of per capita national income. The results also indicated a strong positive relationship between (LOG(Y/N)) and the hidden economy index, with a regression coefficient of (+1.215), which was significant at 1%. There was a weak positive relationship between inflation and the hidden economy, with the estimated coefficient of LOG(INF) being (+0.556) and statistically significant at the 10% level. There is a cointegration relationship between the variables, indicating a stable equilibrium relationship in the long term between the size of the hidden economy and the explanatory variables. The variance decomposition analysis results for the two variables (LOG(TAX) and LOG(Y/N)) contributed significantly to explaining the variance of the C/M index. The study recommended the necessity of enhancing financial oversight and transparency tools by expanding the electronic invoicing system, broadening financial inclusion, and digital transformation. It also recommends conducting detailed field research in sectors where the hidden economy appears.